Clinical Profile of COVID-19 Illness in Children—Experience from Tertiary Care Hospitals - Rubab Munawar, Hina Shafi, Asia Hussain, Tahira Qadeer, Varda Balouch, Rubab Rameez, Rana Khurram Aftab, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Assessing detailed clinical profile as well as outcome in severe acute respiratory infection coronavirus infectious disease 2 (SARS-CoV-2) infected children. Methods: This is a retrospective study undertaken at pediatric departments of tertiary care hospitals of Lahore, Rawalpindi and Mirpur AJK for the period of three months from July 2021 to September 2021. The clinical characteristics data as well as result of children under 18 years infected with COVID-19 were reviewed as well as analyzed. Results: In total 2919 children that were suspected to be COVID-19 infected were verified for COVID-19 virus in flu emergency (n = 1744), severe acute respiratory infection ward (n = 825) and non-COVID (n = 350). From these studies, 8.73% children tested positive for COVID-19 infection. Of the positive cases, 56.47% were managed for outpatients and 59% needed admission. Most children admitted had critical illness owing to malnutrition and other comorbidities. Conclusions: Children of any age group are vulnerable to COVID-19 with minor male preponderance. Amongst infected, 2/3rd were asymptomatic or mildly symptomatic and needed outpatient management as well as home isolation. The adverse consequences were commonly observed in infants as well as children under 10 years of age with undernourishment and comorbidity.